Clinically derived 12-factor structure and confirmatory factor analysis of the neurodevelopmental parent report for outcome monitoring - Baumer, Nicole T.; Pawlowski, Katherine G.; Amaral, Joseph L.; Zhang, Bo; Sideridis, Georgios; Levin, April R. (Frontiers in Psychiatry, 2023)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by social communication and social interaction impairments accompanied by restrictive and repetitive behaviors or interests. Co-occurring conditions may greatly impact overall functioning and intervention needs, and contribute to individual variability and etiologic subtypes. Clinical care of individuals with ASD requires gathering a breadth of information across multiple domains. The Neurodevelopmental Parent Report for Outcome Monitoring (ND-PROM) was developed to assess symptoms across core features of ASD as well as frequent concerns and comorbidities. The current study expands upon the initially reported psychometric properties of the ND-PROM and evaluates a proposed a clinically derived 12-factor structure of the ND-PROM. Methods and Procedures: Participants were 246 children with ASD. The ND-PROM was tested using Confirmatory Factor Analysis (CFA) and measurement invariance based on sex. Outcomes and Results: A 12-factor correlated structure was found (Expressive Language, Receptive Language, Nonverbal Communication, Social Emotional Understanding, Social Interaction, Independent Play, Adaptive/Toileting Skills, Restrictive and Repetitive Behaviors and Interests, Sensory Processes, Challenging Behaviors, Impulse/ADHD, and Mental Health), which did not vary by sex. Conclusions and Implications: The ND-PROM captures a range of distinct aspects of developmental and behavioral functioning in ASD that can be used to track independent functioning across domains.